Online monitoring in the Tagus estuary: Parque das Nações station - Installation and operation between January 2016 and February 2017 - Rodrigues, M. (2017)
This report describes the design and installation of the Parque das Nações online monitoring station and the procedures relative to its maintenance and data verification undertaken between January 2016 and February 2017. This station is equipped with a SEBA MPS D3 multiparameter probe, which measures water levels, conductivity and water temperature, and a SEBA Slimcom2 data logger, for data acquisition and transmission. The data acquired during the period to which this report refers are also briefly presented. This monitoring station is under operation in the scope of the projects H2020 BINGO and FCT UBEST.